Quintessential Conceptualization of Bone Graft (Medico Legal Update, 2021)
As we know that healthy periodontium, is affected in most of the periodontal diseases. Which further leads todamage of hard and soft tissues. To attain back the lost structures the use of bone grafts have shown promisingresults. Managed either by mechanically recontouring it or by grafting techniques. Replacement grafts arewidely accepted as bone formation by promoting for periodontal regeneration . There are many bone graftmaterial which are used as bone substitute to fill the defect site the graft material acts like scaffold on whichbody react it by certain bone mechanism helps to regenerate new bone. This article give an overview onhistory, rationale and objectives of bone replacement grafts, Biology of bone healing, Indications for bonegrafting include, Ideal requirements of bone grafts,List of bone graft according to origin.